Effects of microstructure on high temperature dwell fatigue crack growth in a coarse grain PM nickel based superalloy. (15th May 2015) - Li, H.Y.; Sun, J.F.; Hardy, M.C.; Evans, H.E.; Williams, S.J.; Doel, T.J.A.; Bowen, P.
Abstract: The influence of microstructure on the dwell fatigue crack growth behaviour of an advanced nickel-based superalloy was investigated at a temperature of 700 °C. Microstructural variations were induced by heat treatment variables: different cooling rates of quenching from super-solvus solution heat treatment, 0.7 and 1.8 °C s −1, and an addition of a high temperature stabilisation heat treatment (2 h at 857 °C) between the solution treatment and the final ageing treatment. With a one hour dwell introduced at the peak load of the fatigue cycle, such different microstructural conditions can lead to a difference of up to two orders of magnitude in crack growth rates in air, when compared to those obtained under baseline fatigue loading. By performing such dwell fatigue and baseline fatigue tests in vacuum, it is confirmed that such increases in crack growth rates under dwell fatigue loading in air are mainly environmentally related. Transmission electron microscopy (TEM) was utilised to analyse both crack tip oxides and associated deformation mechanisms in the matrix. A novel mechanism taking into account competing interactions of crack tip oxidation (leading to increases in crack growth rates) and stress relaxation (leading to decreases in crack growth rates) is outlined.